2005
DOI: 10.1002/eji.200526285
|View full text |Cite
|
Sign up to set email alerts
|

A therapeutic vaccine for nicotine dependence: preclinical efficacy, and phase I safety and immunogenicity

Abstract: Nicotine is the principal addictive component in tobacco, and following uptake acts in the central nervous system. The smoking-cessation efforts of most smokers fail because a single slip often delivers sufficient nicotine to the brain to reinstate the drug-seeking behaviour. Blocking nicotine from entering the brain by induction of specific antibodies may be an effective means to prevent such relapses. The hapten nicotine was coupled to virus-like particles (VLP) formed by the coat protein of the bacteriophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
198
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(214 citation statements)
references
References 29 publications
(40 reference statements)
6
198
1
6
Order By: Relevance
“…Additionally, this multimeric complex lacks any viral RNA/DNA and is therefore incapable of replication [168]. Moreover, VLPs can be expressed with additional antigens on or, in the case of polysaccharide or lipid molecules, conjugated to the surface to create a multivalent vaccine [166,[169][170][171]. VLPs contain one or more viral capsid proteins which make up the protective outer shell of a virion and are usually expressed in a eukaryotic cell [110].…”
Section: Virus-like Particlesmentioning
confidence: 99%
“…Additionally, this multimeric complex lacks any viral RNA/DNA and is therefore incapable of replication [168]. Moreover, VLPs can be expressed with additional antigens on or, in the case of polysaccharide or lipid molecules, conjugated to the surface to create a multivalent vaccine [166,[169][170][171]. VLPs contain one or more viral capsid proteins which make up the protective outer shell of a virion and are usually expressed in a eukaryotic cell [110].…”
Section: Virus-like Particlesmentioning
confidence: 99%
“…We have previously demonstrated that highly ordered and repetitive display of antigens on the surface of VLP can induce strong and long lasting B cell responses in mice and humans [28,29]. Hence, it is possible to induce antibodies against self-antigens without the addition of further adjuvants [26,28].…”
Section: Production Of a Qb-il-17 Vaccinementioning
confidence: 99%
“…To successfully neutralize haptens or endogenous small and large soluble polypeptides such as these, it is essential to induce sufficient amounts of high-affinity antibodies. For instance, our current experience indicates that for vaccination against nicotine to be successful, it is necessary to attain levels of nicotine-specific IgG of 10 mg ml [3]. This is orders of magnitude higher than what is usually required for protection against viral infection.…”
Section: The Technologymentioning
confidence: 94%
“…This can be achieved by active vaccination, which induces anti-nicotine antibodies that act to prevent reinstatement of the positive reinforcement resulting from relapse. Proof of concept for this approach has been achieved in animals [3,24]. The mechanism for this is relatively simple.…”
Section: Smoking Cessation Vaccine (A) Introductionmentioning
confidence: 99%
See 1 more Smart Citation